Controlo de elementos de rede para suporte de qualidade de serviço: reconfiguração - Sousa, Luis (2003)
Providing Quality of Service in telecommunication networks covers multiple aspects, including the specific support provided by the equipments. This paper analyses the behavior of CISCO equipments and Linux-based routers in high mobility environments. Weidentify aspects relevant to the reconfiguration of differentiated services structures, in order to minimize the associated reconfiguration time in these high mobility environments. We verified that the choice of QoS tree has a major impact in the final performance of the devices.